2015
DOI: 10.14309/crj.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Severe Sprue-Like Enteropathy Associated With Valsartan

Abstract: Olmesartan sprue-like enteropathy is an adverse drug reaction that mimics the appearance of celiac disease and is related to the use of olmesartan. We present the case of a 71-year-old female with severe enteropathy attributed to celiac disease for 5 years that improved only after valsartan cessation. This is the first case associating valsartan with sprue-like enteropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 13 publications
2
56
0
3
Order By: Relevance
“…A large observational cohort study, based on the French health insurance claim database and using International Classification of Diseases, Tenth Revision (ICD‐10) codes for intestinal malabsorption (IM) and coeliac disease diagnosis, highlighted an increased risk of hospitalization in patients treated with OM when compared with other ARBs and angiotensin converting enzyme inhibitors (ACE‐i) . Otherwise, it is not appropriate to rule out the class‐effect hypothesis because recent case reports suggested an association between severe enteropathy and other ARBs, including valsartan, irbesartan, telmisartan, eprosartan, losartan, and candesartan , . A large population‐based study of ARB‐treated patients managed by the general practitioners in Italy and Germany showed similar low proportions of unspecified IM diagnosis among the different drugs belonging to the same class.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…A large observational cohort study, based on the French health insurance claim database and using International Classification of Diseases, Tenth Revision (ICD‐10) codes for intestinal malabsorption (IM) and coeliac disease diagnosis, highlighted an increased risk of hospitalization in patients treated with OM when compared with other ARBs and angiotensin converting enzyme inhibitors (ACE‐i) . Otherwise, it is not appropriate to rule out the class‐effect hypothesis because recent case reports suggested an association between severe enteropathy and other ARBs, including valsartan, irbesartan, telmisartan, eprosartan, losartan, and candesartan , . A large population‐based study of ARB‐treated patients managed by the general practitioners in Italy and Germany showed similar low proportions of unspecified IM diagnosis among the different drugs belonging to the same class.…”
Section: Introductionsupporting
confidence: 90%
“…11 Otherwise, it is not appropriate to rule out the class-effect hypothesis 12 because recent case reports suggested an association between severe enteropathy and other ARBs, including valsartan, irbesartan, telmisartan, eprosartan, losartan, and candesartan. 10,[13][14][15][16][17][18][19][20] A large population-based study of ARB-treated patients managed by the general practitioners in Italy and Germany showed similar low proportions of unspecified IM diagnosis among the different drugs belonging to the same class. This suggests the absence of differences among different ARBs and shows the very low incidence of IM in association with their intake.…”
mentioning
confidence: 99%
“…The cases of patients with spruelike enteropathy caused by ARBs belonging to the sartan class other than olmesartan are shown in Table 1 45678. Our results indicate that sprue-like enteropathy is associated with the sartan class of ARBs rather than a single drug.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the patients exhibit total or partial villous atrophy, which improves with drug withdrawal 1. Several studies have reported sprue-like enteropathy associated with olmesartan; however, only 5 cases of patients with sprue-like enteropathy associated with telmisartan, valsartan, irbesartan, and eprosartan have been reported thus far 145678. The patient with telmisartan-induced sprue-like enteropathy exhibited ileitis with colitis without the involvement of the duodenum 4.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the NLR has been studied in other conditions, noted as a prognostic marker especially in malignant disease. 2 Recently several studies have identified the NLR as being prognostic in a variety of different liver disease contexts: patients on the liver transplant waiting list, 3 those with low MELD scores, 4 hospitalised patients with cirrhosis, 5 patients with acute-on-chronic liver failure 6 and now patients with decompensated liver disease without acute-on-chronic liver failure. 1 The prognostic value of NLR in these studies appears independent of standard scores of liver function.…”
Section: Linked Contentmentioning
confidence: 99%